Influence of Key Shear Factors on the Shear Performance of Ultra-high Performance Fibre Reinforced Concrete Beam Containing Coarse Aggregate - Smith, Abutu Simon John; Xu, Gang (Periodica Polytechnica Civil Engineering, 2024)
This paper assesses the effect of direct and indirect factors on the shear performance of ultra-high performance fibre reinforced concrete beam containing coarse aggregate (UHPFRC-CA) using four point loading arrangement. The obtained results were used to categorize UHPFRC-CA beam’s failure mode, establish the influence of key factors on shear performance, and develop UHPFRC-CA beam’s compression zone resistance and first shear cracking load equations whose results were compared with those from this research, other researchers and existing equation. Findings revealed that UHPFRC-CA beam fails in cable stayed, shear partial compression, cable stayed-diagonal tension and cable stayed-partial shear tension. Shear span-depth ratio (a/d) has the most influence on the beams’ failure mode. Higher percentage volume of steel fibre improves ultimate load capacity and midspan displacement resistance at failure load. Hooked-end steel fibre improves deformation (crack width and midspan displacement at failure load) resistance. Higher a/d is more beneficial to midspan displacement resistance at failure load than load capacity; while lower stirrup spacing leads to higher midspan displacement at failure load. Finally, the developed first shear cracking load equation can adequately capture the true first shear cracking load of UHPFRC-CA beam; and the developed compression zone resistance equation can be conveniently used to represent the joint contribution of compressive strength and fibre factor to UHPFRC-CA beam’s shear resistance.